APPROACHES TO IDENTIFY VULNERABILITIES IN THE SECURITY SYSTEM OF THE SOCIAL ORGANIZATION AND COMPUTER RESOURCES: APPROACHES TO IDENTIFY VULNERABILITIES IN THE SECURITY SYSTEM OF THE SOCIAL ORGANIZATION AND COMPUTER RESOURCES - Hristov, Hristo; Boyanov, Petar; Trifonov, Tihomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Essential component of organizing stage of the counteraction for the en-croachment against the business organization is to identify vulnerabilities of the social organization. The purpose of this stage is to identify all existing and potential weaknesses and disadvantages of the security system of the organization, creating a circumstance for adversely effects on the sources of threat.